Bacteremia Caused by Kocuria kristinae from Egypt: Are There More? A Case Report and Review of the Literature - Reem M. Hassan; Dina M. Bassiouny; Yomna Matar (Case Reports in Infectious Diseases)
Kocuria kristinae is opportunistic Gram-positive cocci from the family Micrococcaceae. It is usually considered part of the normal flora that rarely is isolated from clinical specimens. Here, we report a case of Kocuria kristinae bacteremia; to the best of our knowledge, this is the first report from Egypt.